A study of the undergraduate library science programs in selected library schools in Metro Manila with implications on the education of information professionals and curriculum development - Madrid, Jennifer M. 1969-
The study concludes that: 1) the curricular offerings in selected library schools studied are tailored toward producing librarians but gradually changing toward producing information professionals; 2) most of the library science graduates believe that the knowledge and training they had in school is sufficient in terms of answering the needs in their present jobs; 3) most of the library administrators indicate that library science subjects in the present curriculum are still very important based on the needs and activities of their respective libraries; 4) the dean/heads of library schools are aware that there is still room for improvement in the areas of facilities/equipment for the program, and method of administering these courses; 5) most of the library administrators say that a bachelor's degree in library and information science is adequate to get a librarian's job but a lot still needs to be done. One should continue to keep acquiring new skills and knowledge by pursuing graduate studies and/or attending training programs, seminars, and workshops; and, 6) libraries and information centers in the government and private sectors need librarians and information professionals who can handle the information needs of their constituents. The librarians and information professionals should possess the knowledge and training to deal with the tasks assigned to them.